EFFECTIVENESS OF HEALTH PROMOTION USING INSTAGRAM SOCIAL MEDIA TO INCREASE ORAL HEALTH LITERACY IN BANJARBARU SOUTH KALIMANTAN - Dinda Andira Salsabila; Rosihan Adhani; Isnur Hatta (Dentin, 2023)
Background: Banjarbaru is the city with the lowest percentage in the South Kalimantan region regarding knowledge the ease of access to dental health services. This shows an illustration of the importance of health promotion so that people are more aware of the importance of maintaining dental and oral health. One strategy to achieve optimal health promotion is to use health promotion methods through social media. Instagram social media as a health promotion media has the advantage of being easy to access without being constrained by distance, time, and cost. Purpose: Analyzing the effectiveness of health promotion using Instagram social media to increase oral health literacy in adolescents at  SMP Negeri 1 Banjarbaru. Methods: This studies uses a true experimental design method with a pretest-postest design with control design, the sampling technique is simple random sampling technique. The studies carried out at SMP Negeri 1 Banjarbaru with 92 respondents. Results: There is a difference in the oral health literacy pretest and posttest scores in interverence group, while in the control group there is no significant difference. The significance result of Mann Whitney test in the posttest session for the intervention and the control groups are 0.000 > 0.05 which means that there is a significant difference in oral health literacy scores between the posttest scores of the intervention group and the control group. Conclusion: Health promotion using Instagram social media is effective for improving oral health literacy. Keywords: Health promotion, oral health, oral health literacy, social media